Groundwater-Mixing Mechanism in a Multiaquifer System Based on Isotopic Tracing Theory: A Case Study in a Coal Mine District, China - Pinghua Huang; Xinyi Wang (Geofluids)
Water inrush of mixed groundwater is the primary threat against safe production in coal mines. To study the mixing mechanism of a multiaquifer groundwater system, groundwater samples were collected from different strata in a typical North China-type coalfield (Chaochuan Coal Mine) and were then tested using environmental isotopes (18O, 2H, 3H, 13C, and 14C) and hydrochemical ions (Ca2+, Mg2+, Na+, K+, HCO3−, SO42−, and Cl−) as tracer agents. Results demonstrate that HCO3− and Cl− exhibit a linear relationship with the mixing ratio, whereas Na+, Ca2+, and SO42− show certain degrees of curvature. This condition indicates that groundwater mixing involves major chemical actions. The δD–δ18O plot reveals that karst water and groundwater from Quaternary and sandstone aquifers are mainly mixtures of local rainfall, evaporated groundwater, and “palaeo-groundwater.” The 3H < 0.5 TU and 14C content in the groundwater sample number 27 is 13.6 pmc, which suggests that this groundwater sample is the last rainfall recharge in the ice stage. Palaeo-groundwater in a sandstone aquifer accounts for more than 60%, and that in the Cambrian limestone aquifer is lower than 20%. Groundwater from the Quaternary aquifer is supplied by “modern” rainfall. The δ13C of groundwater from a sandstone aquifer decreases with the increase in CO32− + HCO3−, and this condition reflects that organic matters exhibit biological degradation reaction. However, δ13C increases with the rise in CO32− + HCO3− in the Cambrian limestone groundwater, and this condition indicates that organic matters produce methane due to methanogens.